Enhancing Students' Problem-Solving Skills through the PBL Model assisted with the Media of Local Wisdom Mathematical Snakes and Ladders - Febila, Dela; Riswari, Lovika Ardana; Fardhani, Much Arsyad (Universitas Pendidikan Indonesia Kampus Serang, 2024)
Problem-solving skills are the most basic thing that students must have as they can train students to deal with various existing problems in learning. The background to this research is the students’ low problem-solving skills in the learning process in the classroom. This research, thus, aims to improve problem-solving skills in mathematics subjects through the Problem-Based Learning model with the help of Local Wisdom Mathematical Snakes and Ladders media. This classroom action research was conducted at Birrul Walidain Muhammadiyah Elementary School, with 28 students as research subjects. This research was carried out in two cycles, each cycle consisting of four stages: planning, implementation, observation, and reflection. The data were obtained through tests, observation, interviews, and documentation. The data were then analyzed quantitatively and qualitatively. The research results demonstrated that problem-solving skills could increase with each cycle. This could be observed from the research results, proving that students' problem-solving skills achieved success of 32.14% in the pre-cycle, reached 71.42% in cycle I, and increased to 85.71% in cycle II. Based on their effectiveness, the Problem-Based Learning model and the Local Wisdom Mathematical Snakes and Ladders learning media implemented can be employed as a recommendation for class teachers in carrying out learning since they can help students be more active and improve their ability to think critically and solve real problems.